The labor market consequences of internal migration in Turkey - Ali Berker (TÜSİAD-Koç University Economic Research Forum, 2010)
During the last 30 years, Turkey has undergone profound economic and social transformations, including fundamental shifts from the state-oriented economy to the market-oriented economy; large scale modernization investments in telecommunication and transportation services; and the low-intensity ongoing armed-conflict concentrated in the country's Southeastern Region. For such a period, using the 1990 and 2000 Turkish Censuses, I evaluated the labor market consequences of internal migration that might have been sparked by such significant economic and social changes. Overall, the results suggest that provinces with a higher share of recent migrants may observe decreases in their native population' labor market opportunities. While this adverse impact of the recent migrant inflows remains to be robust, it exhibits heterogeneity with respect to the skill level of natives, as well as for the labor market outcomes of different native and migrant groups.
Keywords: 330; internal migration; labor market outcomes; Turkey; Binnenwanderung; Beschäftigungseffekt; Sozialer Wandel; Türkei